Intradialytic optical assessment of C-mannosyl tryptophan removal using spent dialysate - Paats, Joosep; Adoberg, Annika; Leis, Liisi; Arund, Jürgen; Lauri, Kai; Luman, Merike; Tanner, Risto; Holmar, Jana; Pilt, Kristjan; Fridolin, Ivo (Scientific reports, 2025)
C-mannosyl tryptophan (CMW), also known as C-glycosyltryptophan, is a novel biomarker that is strongly correlated to chronic kidney disease (CKD) incidence and progression risk and mortality among earlier stages of CKD patients prior to end stage kidney disease. This study determined concentrations of CMW in blood and spent dialysate of CKD patients on chronic hemodialysis (HD) for the first time, and investigated the possibility for optical estimation of CMW concentrations in spent dialysate, its intradialytic removal and time-averaged concentration (TAC) of CMW based on optical measurements of spent dialysate. In total, 264 pre- and postdialysis blood samples, and 528 spent dialysate samples from 88 HD sessions of 22 patients were analyzed using high pressure liquid chromatography and spectrophotometry. We identified that CMW concentrations in CKD patients on chronic HD are over 10 times higher compared to earlier reported CMW concentrations in healthy subjects. The concentration of CMW in spent dialysate can be monitored based on spectrophotometric analysis of spent dialysate (r > 0.939, standard error: 0.07 μmol/L) and it is possible to evaluate CMW-based HD adequacy parameters, such as reduction ratio, mass of total removed solute, and TAC without blood sampling. In future, optical monitoring of CMW could be potentially used to improve clinical management of hemodialysis patients.